PERBANDINGAN ANTARA PENGGUNAAN KAPUR DAN ABU SEKAM PADI UNTUK STABILISASI TANAH DASAR - Dwi Nuryasin; Gerard Aponno; Moch Sholeh (Prokons: Jurnal Teknik Sipil, 2019)
The subgrade used for road construction should have a good bearing capacity, because the loads applied on the road construction are static and dynamic loads. If the CBR (California Bearing Ratio) value low so the subgrade of bearing capacity is not good. The purpose is to get the results of physical of the original soil, get the value of CBR laboratory of the original soil, get the CBR laboratory that has been stabilized using lime and rice husk ash, find out the optimum needs of lime and rice husk ash.Four original soil samples each of lime and rice husk had to go through an experiment by using 5%, 8%, 10% and 12% of lime and rice husk ash.  The experiment results in water content w = 58.12%, weight of the soil γt= 1.44 grm/cm3, specific gravity Gs=2.11, Liquid Limit LL = 67.28%, Plastic Limit PL=54.06%, Plasticity Index =13.21%, maximum dry matter weight = 1.342 gr/m3 CBR= 5.13% physical properties of original soil; medium plasticity properties; 10% maximum CBR value at 69.046% lime; 10% maximum CBR value at 8.476% rice husk ash. Keywords: lime, rice husk ash, stabilization, CBR